Novel polyhydroxyalkanoate–graphene oxide composites with potential for clinical application against bacterial implant-associated infections in septic surgery - Paxinou, A.; Nigmatullin, R.; Paterakis, G.; Sygellou, L.; Viebahn, R.; Galiotis, C.; Salber, J.; Roy, I. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionImplant-associated infections are a major clinical challenge, often leading to implant failure, revision surgeries, and increased healthcare costs. The development of advanced biomaterials with inherent antimicrobial properties is critical to address this issue. In this study, we present novel two-dimensional (2D) composite films based on polyhydroxyalkanoates (PHAs) combined with graphene oxide (GO) to confer both antimicrobial activity and tailored mechanical properties.MethodsComposites with varying GO concentrations (0.5, 2, and 5 wt%) were fabricated using the solvent casting method, using both a short-chain-length PHA, P(3HB) and a medium-chain-length PHA, P(3HO-co-3HD). Physicochemical characterization (scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, X-ray diffraction (XRD), differential scanning calorimetry (DSC), and mechanical testing) confirmed successful GO incorporation, changes in surface morphology, and modifications in thermal and mechanical properties.ResultsNotably, the incorporation of 2 wt% GO into P(3HB) increased the Young’s modulus from 776 ± 15 MPa to 1,055 ± 28 MPa, indicating enhanced stiffness. Antibacterial testing using ISO 22196 against Staphylococcus aureus and Escherichia coli revealed that P(3HB)/2 wt% GO exhibited the highest antibacterial efficacy. In contrast, the 5 wt% GO composite showed reduced antibacterial activity, likely due to GO agglomeration. Moreover, in vitro cytocompatibility assays using L929 fibroblasts and NG108-15 neuronal cells demonstrated high cell viability across all composites, indicating high cytocompatibility.Discussion/ConclusionThese findings highlight the potential of PHA/GO composites as sustainable, antimicrobial biomaterials for future use in implantable devices for septic surgical applications.